Sound isolation provided by shading screens applied in façades - Jorge Emanuel Matos da Silva (2010)
In most European countries, legislation exists about airborne sound insulation in dwellings, including facades. Mainly in southern Europeans countries, the glazed windows of building facades normally have shading systems to minimize the excessive heating of interior rooms due to the solar rays incidence and to provide for darkening of the room. The effect regarding sound isolation of those shading systems is usually not analyzed in the buildings acoustic project. This study presents values of weighted sound reduction index (Rw) provided by several shading system types (outside screens and interior screens) and presents a simple model to predict their sound reduction index.